Low-field nmr methods applied to the characterization of coconut cream - Antony, Jürgen H. (2016)
Several low-field NMR methods in combination were applied to investigate the flow properties, stability and drying behavior of coconut cream. From measurements of NMR relaxation in confined samples, insight into the creaming stability of the emulsions was obtained in a non-invasive manner; the multiphase structure of a creamed emulsion was visualized with 1D-NMR imaging; the flow behavior of the (homogenized) emulsion was measured by means of rheo-NMR, leading to a power law index 0.61 in an Ostwald-de-Waele model. The drying and the role of creaming in this process were followed with depth resolution through profiling NMR.